Engineering allosteric inhibition of homoserine dehydrogenase by semi-rational saturation mutagenesis screening - Liu, Xinyang; Liu, Jiao; Liu, Zhemin; Qiao, Qianqian; Ni, Xiaomeng; Yang, Jinxing; Sun, Guannan; Li, Fanghe; Zhou, Wenjuan; Guo, Xuan; Chen, Jiuzhou; Jia, Shiru; et al. (Frontiers in Bioengineering and Biotechnology, 2024)
Allosteric regulation by pathway products plays a vital role in amino acid metabolism. Homoserine dehydrogenase (HSD), the key enzyme for the biosynthesis of various aspartate family amino acids, is subject to feedback inhibition by L-threonine and Lisoleucine. The desensitized mutants with the potential for amino acid production remain limited. Herein, a semi-rational approach was proposed to relieve the feedback inhibition. HSD from Corynebacterium glutamicum (CgHSD) was first characterized as a homotetramer, and nine conservative sites at the tetramer interface were selected for saturation mutagenesis by structural simulations and sequence analysis. Then, we established a high-throughput screening (HTS) method based on resistance to Lthreonine analog and successfully acquired two dominant mutants (I397V and A384D).Compared with the best-ever reported desensitized mutant G378E, both new mutants 34 2 qualified the engineered strains with higher production of CgHSD-dependent amino acids. The mutant and wild-type enzymes were purified and assessed in the presence or absence of inhibitors. Both purified mutants maintained >90% activity with 10 mM Lthreonine or 25 mM L-isoleucine. Moreover, they showed >50% higher specific activities than G378E without inhibitors. This work provides two competitive alternatives for constructing cell factories of CgHSD-related amino acids and derivatives. Moreover, the proposed approach can be applied to engineering other allosteric enzymes in the amino acid synthesis pathway.